(untitled) (Journal of Applied and Natural Science, 2018)
Cherry tomato (Solanum lycopersicon var cerasiforme) is small size fruits, with a bright red colour resembling to cherry and becoming popular in the retail chains which are marketed at a premium price. The field experiment was conducted to study the effect of different (35, 50 and 75 per cent) shading intensities on growth and yield (qha-1 ) of cherry tomato. Significantly maximum yield was recorded in 35 per cent shading intensity and genotype Kalash Seeds Product (KSP)-113 (579.44 and 503.88 q ha-1 , respectively). Among the different shading intensities and genotypes, maximum plant height was observed in 75 per cent shading intensity and genotype KSP -113 at 30 days interval (74.70 and 60.95 cm, respectively). The minimum days to 50% flowering of cherry tomato were observed in cherry tomatoes grown under 35 per cent shading intensity (45.00 days) as compared to other shading intensities while minimum days to 50% flowering were observed in genotype KSP-113 (44.00 days). The maximum length of the cluster (9.58 cm), the weight of cluster (27.67 g), number of fruits per cluster (9.42) and number of pickings (11.67) were observed in 35 per cent shading intensities and in genotype KSP-113. The cultivation of KSP-113 genotype under 35 per cent shading intensity was found to be most sustainable for improving growth and yield of cherry tomato during the summer season.